CREB1T: A Gamification of Double Entry Accounting System Based on Android Application - Erienika Meiling Lompoliu (CogITo Smart Journal, 2020)
All is altered by technology. Every aspect of our lives is now, in one way or another, heavily dependent on or seamlessly improved by technology. Different technology media, channels and resources, especially in the higher education, have greatly affected the method of pedagogy in recent years. First was computer-based learning, which has replaced most of the traditional way in reading, learning and test taking. This include the use of electronic books, videos and the computer-based exams. On the other hand, gamification has been able to enhance students' understanding of learning. From the usual monotonous reading to the recollection of a enjoyable game-like experience, which gives them the feeling of pleasure instead of pressure. The students undertaking accounting classes have a great deal to learn basic accounting including debit and credit principles – a double entry accouting system method, which are one of the essentiaal and important to the skills they have in the real world, and yet they can be repetitive, boring and tearful. The CREB1T application aimed to tackle this issue by incorporating gamification approach in the lesson and deploy it on a mobile application, a platform where most millenials students are receptive with. And since it’s on mobile students may able to learn it anywhere during their spare time giving them freedom to suit their study habit.